اندلسی مسلم دور حکومت میں مسلم و غیر مسلم سماجی تعلقات: Muslim and non-Muslim social relations during Spainish Muslim rule - Dr Shabir Ahmad Jamee; Muhammad Abu Bakar; Suleman Saleem (International Research Journal of Arabic and Islamic Studies, 2024)
In Spain, where the Muslims expanded their empire and filled the coffers of their government, they also served humanity and indeed proved to be the saviors of the people of Spain. The Muslim conquest of Spain brought about important changes in every sphere of life. In the beginning, it was believed that the Muslims attacked only for the sake of booty. But when they started settling their settlements and building mosques, Gath was convinced that they were doomed forever. The Muslims gave full proof of their traditional tolerance. The new rulers not only fully protected the slaves and peasants, but treated them with complete justice, after ensuring the payment of tribute and obedience. Christians and Jews enjoyed full religious freedom. There was no interference in their religious affairs. In this paper, Muslim and non-Muslim social relations have been reviewed during the Andalusian Muslim rule.